High‐versus low‐dose clonidine for sedation and analgesia in critically ill adults: A retrospective cohort study. (27th August 2021) - Purivatra, Elsa; Guenette, Melanie; Coleman, Brenda; Cheung, Alexandra; Burry, Lisa
Abstract: What is known and objective: Limited data suggest clonidine may be useful for sedation and analgesia in critically ill patients. Our objectives were to describe clonidine dosing regimens used for sedation and analgesia in critically ill adults, the associated adverse effects (i.e., hypotension), and whether clonidine dose was associated with dosage reductions of traditional sedatives and analgesics. Methods: We conducted a retrospective cohort study of all critically ill adults who received enteral clonidine for sedation and analgesia during a five‐year study period (2011–2016). We categorized patients as low‐dose (LD ≤0.4 mg/day) or high‐dose (HD >0.4 mg/day) based on the maximum total daily clonidine dose. Results and Discussion: In total, 166 patients received clonidine for sedation analgesia; the median age was 56 years, 36% were female, and 96% were mechanically ventilated (median 10 days). Eighty‐eight patients (53%) received HD clonidine. There were no significant differences in hypotension, bradycardia, rebound hypertension or tachycardia between groups. The HD group had a greater reduction in mean daily opioid requirements throughout clonidine use compared with the LD group (−218.8 mcg vs. −42.5 mcg fentanyl equivalents, p = 0.049), while antipsychotic doses increased (5.7 mg vs. 0 mg olanzapine equivalents, p = 0.04) and sedative doses did not differ. What is new and conclusions: Clonidine doses >0.4 mg/day were associated with a decrease in patients' opioid but not sedative requirements without causing significant adverse effects. Antipsychotic doses increased in conjunction with HD clonidine use. Abstract : Clonidine doses >0.4 mg/day were associated with a decrease in patients' opioid but not sedative requirements without causing significant adverse effects. Antipsychotic doses increased in conjunction with HD clonidine use.